Yes‐associated protein/TEA domain family member and hepatocyte nuclear factor 4‐alpha (HNF4α) repress reciprocally to regulate hepatocarcinogenesis in rats and mice. Issue 4 (19th December 2016) - Cai, Wang‐Yu; Lin, Ling‐Yun; Hao, Han; Zhang, Sai‐Man; Ma, Fei; Hong, Xin‐Xin; Zhang, Hui; Liu, Qing‐Feng; Ye, Guo‐Dong; Sun, Guang‐Bin; Liu, Yun‐Jia; Li, Sheng‐Nan; et al.
Abstract : Great progress has been achieved in the study of Hippo signaling in regulating tumorigenesis; however, the downstream molecular events that mediate this process have not been completely defined. Moreover, regulation of Hippo signaling during tumorigenesis in hepatocellular carcinoma (HCC) remains largely unknown. In the present study, we systematically investigated the relationship between Yes‐associated protein/TEA domain family member (YAP‐TEAD) and hepatocyte nuclear factor 4‐alpha (HNF4α) in the hepatocarcinogenesis of HCC cells. Our results indicated that HNF4α expression was negatively regulated by YAP1 in HCC cells by a ubiquitin proteasome pathway. By contrast, HNF4α was found to directly associate with TEAD4 to compete with YAP1 for binding to TEAD4, thus inhibiting the transcriptional activity of YAP‐TEAD and expression of their target genes. Moreover, overexpression of HNF4α was found to significantly compromise YAP‐TEAD‐induced HCC cell proliferation and stem cell expansion. Finally, we documented the regulatory mechanism between YAP‐TEAD and HNF4α in rat and mouse tumor models, which confirmed our in vitro results. Conclusion : There is a double‐negative feedback mechanism that controls TEAD‐YAP and HNF4α expression in vitro and in vivo, thereby regulating cellular proliferation and differentiation. Given that YAP acts as a dominant oncogene in HCC and plays a crucial role in stem cell homeostasis and tissue regeneration, manipulating the interaction between YAP, TEADs, and HNF4α may provide a new approach for HCC treatment and regenerative medicine. (Hepatology 2017;65:1206‐1221).